Pertumbuhan dan Keseragaman Warna Bulu Ayam Persilangan Balik (BC2) Hasil Seleksi Genetik Persilangan Ayam Pelung dengan Ayam Pedaging (GROWTH AND PLUMAGE COLOR UNIFORMITY OF BACK CROSS (BC2)CHICKEN RESULTED FROM GENETICS SELECTION OF PELUNG CHICKEN - Perdamaian, Ayudha Bahana I.; Trijoko, Trijoko; Daryono, Budi Setiadi (Jurnal Veteriner; Vol 18 No 4 (2017), 2018)
Research aim to derive an excellent hybrid to be positioned as meat-type chicken. An excellent breed which possess uniform morphological character was archived by genetic selection through back-crossed mating shceme in focus on growth rate and plumage color uniformity. Day Old Chicken (DOC) resulted from parent stock broiler cobb 500 and Pelung chicken originated from Cianjur district, West java mating were intensively reared for seven week from hatch. Each chicken weighted every seven day and morphological character assessed at seven weeks old. Observe variable are heterocyst, coefficient Inbreeding (Fx), Inbreeding rate ( F ), plumage and shank characteristic proportion, and its frequency gene alteration through selection. After serial genetic selection, the BC2 chicken has 1129 g body weight and uniform morphological character. Overall body weight of BC3 chicken offspring from BC2 and F1 was deteriorated compared its broiler predecessor because of Inbreeding depression (Fx: 0.4375; F : 0.3125) and heterocyst decrement (H: -39.33) however, morphological appearance were highly resemble pelung chicken. Based on these finding, BC2 chicken was promised meat-type hybrid chicken which has fast growth rate and similar morphological character.